THE FUNCTIONAL ROLE OF DIGITALIZATION IN THE FORMATION OF THE BUSINESS ENVIRONMENT: PERSPECTIVES AND PROBLEMS OF DEVELOPMENT IN UKRAINE - STADNYK, Valentyna; YOKHNA, Vitaliy; NASKALNYJ, Serhij (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Based on the methodological approaches of the theory of entrepreneurial society and institutional economic theory, the author’s definition of the term "business environment" is formulated as a system of relations between economically active members of society, which is formed under the influence of formalized (legislative and legal norms) and informal (customs, traditions, mentality) regulatory institutions that determine the principles of economic interaction in the triad of stakeholders "business-state-society", balancing public and private interests and delineating the field of economic activity in the system of coordinates "knowledge-needs-resources-security". The problems of the functioning of small and medium-sized businesses caused by the institutional imperfection of the domestic business environment and the conditions under which it can become a driver of socio-economic progress are highlighted. Their information base is indicated, which ensures, firstly, the formation of a clear structure of the legislative and regulatory component of entrepreneurial activity, which should contain economic preferences differentiated by time and types of economic activity, corresponding to the interests of society and conceptually defined priorities of its development; secondly, free and prompt access of the economically active population to information that outlines the criterion parameters of additional institutional support for innovative business projects in the "needs-resources-security" coordinates. It is argued that the digitalization of the business environment plays an important role in creating these conditions - as a set of processes and means of information support for business functioning. The contours and directions of development of the multi-component functionality "digitalization" in the processes of forming such an entrepreneurial environment, under which small and medium-sized businesses can become the backbone of economic stability and the driving force of Ukraine in its post-war revival, are outlined.